PEMANFAATAN GOOGLE SITES SEBAGAI PORTOFOLIO PROFESI GURU - Bambang Santoso; Sofa Sofiana; Alvino Octaviano (Abdi Jurnal Publikasi, 2024)
This teacher portfolio creation training using Google Sites aims to improve teachers' digital competence in documenting best learning practices. Through this training, it is expected that teachers will be able to utilize Google Sites features to create professional and interactive portfolios. This portfolio not only functions as proof of performance, but also as a tool for reflection and continuous professional development. The results of this training show a significant increase in teachers' ability to use digital technology for learning purposes and improving the quality of education. This training was conducted by lecturers from Pamulang University to teachers at SDN Keroncong 1 Tangerang, designed to equip teachers with technical skills in using Google Sites. Through presentations, as well as participant observation, the training improved teachers' abilities in designing, developing, and managing digital portfolios. In addition, teachers were also motivated to develop innovative learning practices. The results of this community service concluded that portfolio creation training using Google Sites is an effective step in improving teachers' digital competence and the quality of learning in schools.